Throughput optimisation of inter- and intra-domain autonomous systems traffic engineering. (6th December 2010) - Vidya, K.; Uthariaraj, V. Rhymend
Internet has become a world-wide data network that is used for mission critical applications. The global internet implies several important challenges. The first challenge is the size of the internet which grows enormously in a rapid rate. Hence the traffic on the internet work also increases day to day. Traffic engineering is performed by means of a set of techniques that can be used to better control the flow of packets inside an IP network. This paper proposes a throughput optimisation of both inter- and intra-autonomous systems traffic engineering. Also the optimisation concepts are compared by implementing in various strategies such as sequential, nested and integrated techniques.